MABS composite material and preparation method and application thereof
By introducing wollastonite fibers and oxidized polyethylene wax dispersant into the PMMA/SAN/MBS matrix resin and adopting an oil temperature molding process, the problem of thermoplastic material deformation or cracking under temperature changes is solved, high dimensional stability, good gloss and toughness are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202510119984.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-25
- Publication Date
- 2025-04-25
AI Technical Summary
The existing thermoplastic plastic materials are deformed or cracked due to the abnormal expansion coefficient under the temperature difference change, and the use of glass fibers has problems with floating fibers and high production costs.
Wollastonite fibers and oxidized polyethylene wax dispersant were introduced into the PMMA/SAN/MBS matrix resin for composite processing, and an oil temperature molding process was adopted to achieve high dimensional stability and good gloss.
The product is achieved with high dimensional stability, good gloss and sufficient toughness, avoiding the problem of gate whitening, reducing production costs and improving production efficiency.
Smart Images

Figure BDA0005258666960000071 
Figure BDA0005258666960000072 
Figure BDA0005258666960000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a MABS composite material and a preparation method and application thereof. Background Art
[0002] Electronic appliances with screens (such as televisions, computer monitors, etc.) generally use thermoplastic materials such as ABS, ABS / PC composite materials, etc. as frame materials. However, with the diversification of application scenarios of electronic appliances, in some cases with large temperature differences, the expansion coefficients of existing thermoplastics and metal materials connected to the screen are not synchronized, and the expansion coefficients are high, which may cause the frame materials in the products to deform in high temperature environments and crack in low temperature environments. Especially with the current trend of thinner and lighter electronic appliances, the probability of deformation and cracking is even higher.
[0003] In order to solve the above problems, people add a certain amount of glass fiber to the product to reduce the expansion coefficient of the product. However, due to the floating fiber problem of glass fiber, specific steam molding is required to achieve a better appearance. However, steam molding causes great damage to the mold and requires frequent polishing, which seriously affects production efficiency and leads to high production costs. At the same time, the impact resistance of the prepared products still needs to be improved. Some other types of fillers, if added improperly, are very likely to cause uneven dispersion, so that obvious whitening appears at the gate. Summary of the invention
[0004] Based on the defects of the prior art, the purpose of the present invention is to provide a MABS composite material, which is compounded by introducing specific wollastonite fibers and oxidized polyethylene wax dispersant into PMMA / SAN / MBS (polymethyl methacrylate / poly(styrene-acrylonitrile) / methyl methacrylate-butadiene-styrene polymer) matrix resin. The product can achieve high dimensional stability by adopting a conventional oil-temperature mold forming process. At the same time, the product can meet the requirements of appearance gloss, will not have the problem of whitening of the gate, and has sufficient toughness for use.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] A MABS composite material comprises the following components in parts by weight:
[0007] 30-60 parts of PMMA resin, 20-40 parts of SAN resin, 15-30 parts of MBS resin, 10-30 parts of wollastonite fiber, 0.5-2 parts of oxidized polyethylene wax type dispersant and 0.1-1 part of lubricant.
[0008] In order to overcome the problem of deformation and cracking of products caused by thermal expansion and contraction due to changes in ambient temperature, fillers such as glass fiber are generally added to the existing frame materials used to prepare products with display screens such as televisions to improve the dimensional stability of the products. However, glass fiber itself has the problem of floating fibers, which in turn affects the appearance. Therefore, it is necessary to use steam molding and polishing processes, which increases the production cost of the product and reduces the production efficiency. At the same time, the introduction of glass fiber will also affect the mechanical properties of the product, reducing the toughness of the product. On the other hand, some conventional fillers are prone to uneven dispersion if added too much, so that obvious whitening occurs at the gate. To this end, in the technical solution of the present invention, PMMA / SAN / MBS system resin is used as the matrix resin so that the product first has a high glossiness, and then a specific one-dimensional filler wollastonite fiber is compounded with a specific oxidized polyethylene wax type dispersant as a functional component. Compared with glass fiber, wollastonite fiber will not have floating fiber phenomenon under the dispersion system, and has high dispersibility, which can take into account the effects of improving product dimensional stability and avoiding excessive reduction in glossiness. The product has a low linear expansion coefficient and can be injection molded using a low-cost and high-efficiency oil temperature mold molding process with high glossiness. At the same time, under the action of the oxidized polyethylene wax type dispersant, the product has sufficient toughness for use, and will not have the problem of whitening of the gate during molding, and has a good appearance and excellent comprehensive performance.
[0009] Preferably, the MABS composite material comprises the following components in parts by weight:
[0010] 35-50 parts of PMMA resin, 25-35 parts of SAN resin, 15-25 parts of MBS resin, 15-25 parts of wollastonite fiber, 0.5-2 parts of oxidized polyethylene wax type dispersant and 0.3-1 part of lubricant.
[0011] Preferably, in the MABS composite material, the total mass content of PMMA resin, SAN resin and MBS resin is ≥ 60wt%.
[0012] Preferably, the PMMA resin has a melt flow rate of 1 to 20 g / 10 min at 230° C. and a load of 3.8 kg according to ISO 1133-2011.
[0013] More preferably, the melt flow rate of the PMMA resin at 230° C. and 3.8 kg load is in the range of one or any two of 1 g / 10 min, 4 g / 10 min, 5 g / 10 min, 8 g / 10 min, 10 g / 10 min, 12 g / 10 min, 16 g / 10 min, and 20 g / 10 min.
[0014] Preferably, the SAN resin has a melt flow rate of 25 to 60 g / 10 min at 220° C. and a load of 10 kg according to ISO 1133-2011.
[0015] More preferably, the melt flow rate of the SAN resin at 220° C. and under a load of 10 kg is in the range of one or any two of 25 g / 10 min, 30 g / 10 min, 35 g / 10 min, 40 g / 10 min, 45 g / 10 min, 50 g / 10 min, 55 g / 10 min, and 60 g / 10 min.
[0016] Preferably, the MBS resin is a core-shell structure particle, the core includes rubber, and the average particle size of the core is 200-300 nm.
[0017] More preferably, the average particle size of the inner core of the MBS resin refers to the characterization method described in "Synthesis and Standards of MBS Resin" - Ning Lihong, and the resin is diluted with deionized water and ultrasonically oscillated, then dried, stained with OsO4, and then observed with a transmission electron microscope, and Image J image analysis software is used to analyze the particle size of at least 50 rubber inner cores to calculate the average value.
[0018] Preferably, the average retention length of the wollastonite fibers is 10 to 60 μm.
[0019] More preferably, the retained average length of the wollastonite fibers is in the range of one or any two of 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, and 60 μm.
[0020] More preferably, the average retention length of the wollastonite fibers is 15 to 45 μm.
[0021] It should be noted that the retained average length of the wollastonite fiber described in the present invention can be adjusted by a variety of methods, including adjusting the screw speed, material feed rate, the number, angle, combination and other parameters of the shear blocks in the screw combination when the product is melt-extruded, and can also be achieved by adjusting the gap between the screw and the barrel, etc. It is not limited to one method and needs to be determined based on the specific feasible operations of the actual operator.
[0022] As a key component of the MABS composite material, the use of wollastonite fiber is irreplaceable. During the screening, the inventors found that the average retained length of wollastonite fiber in the product is related to the toughness and appearance performance of the product. Within the above preferred range, the product can have both better toughness and appearance effects.
[0023] Preferably, the test method for the retained average length of wollastonite fibers in the MABS composite material of the present invention is: calcining the MABS composite material at 800°C for 30 minutes in an air atmosphere, then taking the ash and ultrasonically dispersing it in water for 20 minutes, then searching for wollastonite fibers under an optical microscope and screening at least 200 wollastonite fibers for length measurement, and calculating the average value, which is the retained average length of the wollastonite fibers.
[0024] Preferably, the oxidized polyethylene wax type dispersant includes at least one of oxidized polyethylene wax and acid-modified oxidized polyethylene wax.
[0025] More preferably, the density of the oxidized polyethylene wax dispersant is 900 to 1000 kg / m 3 .
[0026] More preferably, the density of the oxidized polyethylene wax dispersant is 900 kg / m 3 , 920kg / m 3 , 940kg / m 3 , 960kg / m 3 、980kg / m 3 , 1000kg / m 3 The range value of one or both of them.
[0027] Preferably, the acid value of the oxidized polyethylene wax-type dispersant is 15 to 65 KOH mg / g.
[0028] More preferably, the acid value of the oxidized polyethylene wax-based dispersant is in the range of one or any two of 15KOH mg / g, 20KOH mg / g, 25KOH mg / g, 30KOH mg / g, 40KOH mg / g, 45KOH mg / g, 50KOH mg / g, 60KOH mg / g, and 65KOH mg / g.
[0029] Preferably, the acid value of the oxidized polyethylene wax-type dispersant is obtained by testing using ASTM D1386-15-2022.
[0030] Preferably, the lubricant includes at least one of ethylene bisstearamide and pentaerythritol stearate.
[0031] In the technical solution of the present invention, in order to ensure the dispersibility of wollastonite fiber in the organic resin matrix during the processing of the product and to ensure the basic mechanical toughness of the product, it is necessary to use an oxidized polyethylene wax dispersant and a lubricant in combination. If only conventional lubricants are used, the expected performance of the product cannot be achieved.
[0032] Preferably, the mass ratio of the lubricant to the oxidized polyethylene wax-type dispersant is (5-7):(8-10).
[0033] As a lubricant and an oxidized polyethylene wax-type dispersant, both can improve the dispersibility and compatibility of wollastonite fiber in the product. When the ratio of the two components is preferably within the above range, the product can achieve better component uniformity and better overall performance.
[0034] It should be noted that the components of the product of the present invention also include 0.01 to 1 parts of functional additives. More preferably, the processing aids include antioxidants, antistatic agents, etc. Those skilled in the art can add them according to actual needs as long as they do not affect the expected technical effects of the product of the present invention.
[0035] More preferably, the components of the MABS composite material also include 0.2 to 1 parts of antioxidant.
[0036] More preferably, the antioxidant includes at least one of a hindered phenol antioxidant and a phosphite antioxidant.
[0037] Another object of the present invention is to provide a method for preparing the MABS composite material, comprising the following steps:
[0038] After the components are uniformly mixed, they are melt-extruded and granulated in a screw extruder to obtain the MABS composite material.
[0039] The preparation method of the MABS composite material of the present invention has simple operation steps and can realize industrial-scale production.
[0040] Preferably, the temperature range of the screw extruder is set to: 180-240°C, the screw speed is 200-800r / min, and the screw aspect ratio is 36-48:1.
[0041] Another object of the present invention is to provide application of the MABS composite material in the preparation of electronic appliances with screens.
[0042] Preferably, the electronic appliances with screens include televisions, computer monitors, and projectors.
[0043] Another object of the present invention is to provide an electronic appliance with a screen, wherein the electronic appliance comprises a screen supporting component, and the screen supporting component comprises the MABS composite material of the present invention.
[0044] Due to the composite use of wollastonite fiber and oxidized polyethylene wax type dispersant, the MABS composite material of the present invention can directly adopt a low-energy consumption and high-efficiency oil temperature mold process during injection molding, and has a high production cost performance; the plastic parts prepared with the material have high dimensional stability, are less affected by external temperature factors, have no appearance problems, have ideal glossiness, and meet normal toughness requirements, so they are very suitable for preparing supporting parts such as screens in electronic appliances.
[0045] The beneficial effect of the present invention is that the present invention provides a MABS composite material, which is compounded by introducing specific wollastonite fiber and oxidized polyethylene wax type dispersant into PMMA / SAN / MBS matrix resin. The product can achieve high dimensional stability by adopting a conventional oil temperature mold forming process. At the same time, the product can meet the requirements of appearance gloss, will not have the problem of whitening of the gate, and has sufficient toughness for use. DETAILED DESCRIPTION
[0046] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0047] Examples 1 to 13
[0048] The MABS composite material and the preparation method and application thereof of the present invention are described in an embodiment. The components of the MABS composite material are shown in Table 1.
[0049] The preparation method of the product comprises the following steps:
[0050] The components are mixed uniformly, and then placed in a screw extruder for melt extrusion and granulation to obtain the MABS composite material.
[0051] The temperature zones of the screw extruder are set as: zone 1: 200°C, zone 2: 200°C, zone 3: 220°C, zone 4: 220°C, zone 5: 200°C, zone 6: 200°C, zone 7: 210°C, zone 8: 210°C, zone 9: 200°C, zone 10: 220°C, the screw speed is 400r / min, and the aspect ratio is 40:1.
[0052] Among them: Process 1 is that wollastonite fiber is added from the feeding port on the side of the screw barrel in the fifth zone; Process 2 increases the shear strength of the screw combination by increasing the number of high-angle shear screw blocks to reduce the retention length of the wollastonite fiber, and the wollastonite fiber is fed from the side of the screw barrel in the fifth zone; Process 3 uses the same screw combination as Process 2, and the fiber is added from the main feeding port in the first zone.
[0053] In a specific embodiment of the present invention, the average length of wollastonite fibers retained in the prepared MABS composite material is adjusted by different processes.
[0054] Comparative Examples 1 to 6
[0055] The difference between the comparative examples and the embodiments is only in the types and proportions of components, as shown in Table 2.
[0056] Among the components described in each embodiment and comparative example,
[0057] PMMA resin 1 is CM-205 produced by Chimei, with a melt flow rate of 2 g / 10 min at 230 °C and 3.8 kg load;
[0058] PMMA resin 2 is CM-211 produced by Chimei, with a melt flow rate of 16 g / 10 min at 230 °C and a load of 3.8 kg;
[0059] SAN resin 1 is AS SA30 produced by LG Chemical, with a melt flow rate of 28 g / 10 min at 220 °C and 10 kg load;
[0060] SAN resin 2 is AS SA50 produced by LG Chemical, with a melt flow rate of 55 g / 10 min at 220 °C and 10 kg load;
[0061] MBS resin 1 is EM520 produced by LG Chemical, and the average particle size of the rubber particles as the core is 200nm;
[0062] MBS resin 2 is EM530 produced by LG Chemical, and the average particle size of the rubber particles as the core is 300nm;
[0063] Wollastonite fiber 1 is produced by NYCO 4W, average length is 65um;
[0064] Wollastonite fiber 2 is HJMF-BAKF produced by Huajietai Mine, with an average length of 20um;
[0065] Glass fiber produces 988A, continuous fiber for Jushi;
[0066] The talc powder is TY90-13-A produced by Longguang Talc, with an average particle size of 10um;
[0067] Oxidized polyethylene wax dispersant 1 is 1105A produced by Mitsui of Japan, acid modified oxidized polyethylene wax, density 940kg / m 3 , acid value 60KOH mg / g;
[0068] Oxidized polyethylene wax dispersant 2 is AC-316A produced by Honeywell, oxidized polyethylene wax, density 980kg / m 3 , acid value 16KOH mg / g;
[0069] Magnesium stearate dispersant is produced by Hongyuan Chemical, with a density of 1028kg / m 3 , acid value 3.0KOHmg / g;
[0070] (Z)-13-dioctyleneamide dispersant is WK1890 produced by Weike Oil, with a density of 890kg / m 3 , acid value 0.5KOHmg / g;
[0071] Lubricant 1 is commercially available ethylene bisstearamide;
[0072] Lubricant 2 is commercially available pentaerythritol stearate.
[0073] The antioxidant is a compound of a commercially available hindered phenol antioxidant and a commercially available phosphite antioxidant: antioxidant 168 and antioxidant 1010 in a mass ratio of 1:1.
[0074] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, such as antioxidants, lubricants and other processing aids, and anti-dripping agents, and the components and raw materials used in each parallel experiment are all of the same kind.
[0075] Table 1
[0076]
[0077] Table 2
[0078]
[0079]
[0080] Effect Example 1
[0081] In order to verify the performance of the product of the present invention, the following performance tests were performed on the products of each embodiment and comparative example. The specific steps are as follows:
[0082] (1) Notched impact strength test: Tested in accordance with ISO 180-2019 standard, type A notch.
[0083] (2) Gloss test: The sample was injection molded into a 200×10×2 mm square plate using an oil temperature mold at 120-150°C for testing, and then the 60° angle test data was tested and counted according to the standard GB / T 8807-1988.
[0084] (3) Whitening grade test: Each product was injection molded into an observation sample of 200×10×2 mm. The whitening condition of each product was analyzed using shooting software and image processing software. The size of the whitening area was counted as the grade judgment:
[0085] Level 0: The whitening area accounts for ≤0.5%, and the sample is not obviously white;
[0086] Level 1: 0.5%<whitening area≤1%, the surface of the sample is slightly white;
[0087] Level 2: 1%<whitening area≤5%, the surface of the sample is obviously white;
[0088] Level 3: Whitening area>5%, the sample surface is severely whitened.
[0089] (4) Linear expansion coefficient test: According to ISO11359-2-1999, the test was performed using the TMA method.
[0090] The test results are shown in Tables 3 and 4.
[0091] Table 3
[0092]
[0093] Table 4
[0094] Component weight Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 <![CDATA[Notched impact strength (kJ / m 2 )]]> 6.5 7.7 5.6 7.3 6.8 7.5 Glossiness(%) 74 82 81 84 83 82 Whitening level 1 2 2 2 3 2 Linear expansion coefficient um / (m℃) 51 60 68 62 61 69
[0095] It can be seen from Tables 3 and 4 that the product of the present invention can achieve excellent comprehensive performance effects based on the compound use of wollastonite fiber and oxidized polyethylene dispersant, among which the notched impact strength can reach 7.5 KJ / m 2 And above, with good toughness in use, and in terms of appearance, the glossiness of the product after injection molding can reach more than 80%, and the whitening level is maintained at level 0-1, indicating that the product can achieve good appearance under the oil temperature mold injection molding process, and there will be no obvious whitening of the gate during molding; the product has dimensional stability, and the linear expansion coefficient can be maintained below 68um / (m℃), and is less affected by external temperature factors.
[0096] According to Example 1 and Examples 5 to 8, it can be seen that the average length of the wollastonite fiber retained in the product has a certain influence on the performance of the product. When the average length is maintained in the range of 15 to 45 μm, the product can have better toughness and dimensional stability. According to Examples 1 and Examples 10 to 13, it can be seen that in the product, although the amount of dispersant and lubricant added is small, the two work together to ensure the dispersibility and compatibility of the material. Therefore, when the ratio of the two changes, the performance of the product also changes to a certain extent. When the mass ratio of the two is preferably in the range of (5 to 7): (8 to 10), the product has a lower linear expansion coefficient under the condition of higher toughness, and the overall performance of the product is better.
[0097] In contrast, among the comparative examples, the filler used in the product of comparative example 1 is glass fiber. If this filler does not use the steam mold forming process, it will cause the floating fiber phenomenon, which will affect the gloss of the product and the impact resistance is also poor; while the conventional talcum powder filler used in the product of comparative example 2, although the product can achieve sufficient toughness and dimensional stability, the appearance performance is not guaranteed, and the product is more seriously whitened. In addition, talcum powder is far inferior to wollastonite fiber due to its low weld mark strength, so the molded product is very prone to a small amount of bending and breaking, and has poor practicality; the processing aid used in the product of comparative example 3 is only a lubricant, which obviously cannot guarantee the toughness of the product, and cannot achieve sufficient dispersibility and compatibility of wollastonite fiber, the product appearance is seriously whitened, and the dimensional stability is also low; other types of dispersants are used in the products of comparative examples 4 and 5, and it is obvious that these dispersivities are not suitable for the system of the MABS composite material described in the present invention, and the product cannot take into account both the appearance and the toughness in use; however, as shown in comparative example 6, the product cannot only use the dispersant as a functional additive. If the lubricant is missing, the product still cannot achieve the expected effect.
[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A MABS composite material, characterized in that: The composition comprises the following components in parts by weight: 30-60 parts of PMMA resin, 20-40 parts of SAN resin, 15-30 parts of MBS resin, 10-30 parts of wollastonite fiber, 0.5-2 parts of oxidized polyethylene wax type dispersant and 0.1-1 part of lubricant.
2. The MABS composite material according to claim 1, characterized in that: The PMMA resin has a melt flow rate of 1 to 20 g / 10 min at 230° C. and 3.8 kg load according to ISO 1133-2011, and / or the SAN resin has a melt flow rate of 25 to 60 g / 10 min at 220° C. and 10 kg load according to ISO 1133-2011, and / or the MBS has an average particle size of 200 to 300 nm.
3. The MABS composite material according to claim 1, characterized in that: The average retention length of the wollastonite fibers is 10 to 60 μm.
4. The MABS composite material according to claim 1, characterized in that: The oxidized polyethylene wax type dispersant includes at least one of oxidized polyethylene wax and acid-modified oxidized polyethylene wax.
5. The MABS composite material according to claim 1, characterized in that: The density of the oxidized polyethylene wax dispersant is 900-1000 kg / m 3 ; Acid value is 15~65KOH mg / g.
6. The MABS composite material according to claim 1, characterized in that: The lubricant includes at least one of ethylene bis stearamide and pentaerythritol stearate.
7. The MABS composite material according to claim 6, characterized in that: The mass ratio of the lubricant to the oxidized polyethylene wax type dispersant is (5-7):(8-10).
8. The method for preparing the MABS composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: After the components are uniformly mixed, they are melt-extruded and granulated in a screw extruder to obtain the MABS composite material.
9. Use of the MABS composite material according to any one of claims 1 to 7 in the preparation of electronic appliances with screens; preferably, the electronic appliances with screens include televisions, computer monitors, and projectors.
10. An electronic appliance with a screen, characterized in that: The electronic appliance comprises a screen supporting component, and the screen supporting component comprises the MABS composite material according to any one of claims 1 to 7.